Analysis of Product Quality on Interest in Buying Makuku Products - Siti Mabrur Rachmah (MultiTech Publisher, 2023)
The purpose of this study is to determine the effect of Product Quality on Purchase Intention Makuku product. This research uses quantitative research type. The data source of this research is primary data by using consumer and buyer of Makuku as sample. Data were collected by accidental sampling with 40 respondents of Makuku. This study uses simple regression analysis. The findings of this study indicate that the Product Quality significantly influence the Purchase Intention of Makuku.